PENGARUH PENDIDIKAN DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN PT. LABTECH PENTA INTERNASIONAL BATAM - Moben Pakpahan; Sastra Tamami (Universitas Riau Kepulauan, 2015)
The performance of employees is the main factor of an organization in order to achieve the goal of organization. In this study, the factor which affect the employees performance is education and working experience. This study was designed as an empirical study to examine the effect of education and working experience on the performance of employees in PT. Labtech Penta International Batam. Theory used in this study is the theory of Human Resource Management relating to education, working experience, and the performance of employee. This research is descriptive quantitative. Methods of data collection are by questionnaires, literature review and documentation studies. Variables are measured by Likert scale. The population in this study were all employees of PT. Labtech Penta International Batam which has a total employee of 252 with 72 sample people. Result of the first hypothesis shows that the education has positive effect but not significant on the performance of employees with t value ( 1.83 ) and significance ( 0.072 ) 0.005. Result of the second hypothesis shows that working experience has positive and significant effect on the performance of employees with t value 3.12 and significance value 0.003 0.005. The calculation results of the third hypothesis shows that Fcalculation is 8.959 with significance Fcalculation is 0.000 lower than 0.05. Significance 0.000 0.05 means that the influence is significant. In other words, there are significant influence between education and working experience variables on the employee performance variable. In conclusion, education and working experience has positive and significant effect on the employee performance.